The foundations of cross-modal plasticity - Rabinowitch, Ithai (Commun Integr Biol, 2016)
Cross-modal plasticity is a striking adaptive feature of the brain, whereby the loss of one sensory modality induces cortical reorganization that leads to enhanced sensory performance in remaining modalities. Much is known about the macroscopic modifications in the brain that underly cross-modal plasticity and the associated changes in sensory performance. In contrast there is relatively scant information about the molecular and cellular underpinnings of this mechanism. We hypothesized that cross-modal plasticity is a fundamental feature of the nervous system. As such, it should be found in organisms with brains that are substantially less complex than our own. Indeed, we discovered a cross-modal plasticity mechanism in the roundworm Caenorhabditis elegans, whose nervous system is composed of only 302 neurons. Taking advantage of the simplicity of the C. elegans nervous system, we were able to comprehensively study cross-modal plasticity from molecule through circuit to behavior.